Association of Toxicity of Sorafenib and Sunitinib for Human Keratinocytes with Inhibition of Signal Transduction and Activator of Transcription 3 (STAT3) - Yamamoto, Kazuhiro (Public Library of Science, 2014)
Hand–foot skin reaction is a most common multi-kinase inhibitor-related adverse event. This study aimed to examine whether the toxicity of sorafenib and sunitinib for human keratinocytes was associated with inhibiting signal transduction and activator of transcription 3 (STAT3). We studied whether STAT3 activity affects sorafenib- and sunitinib-induced cell growth inhibition in HaCaT cells by WST-8 assay. Stattic enhanced the cell-growth inhibitory and apoptotic effects of sorafenib and sunitinib. HaCaT cells transfected with constitutively-active STAT3 (STAT3C) were resistant to the sorafenib- and sunitinib-induced cell growth inhibition. STAT3 activity decreased after short-term treatment with sorafenib and sunitinib in a dose-dependent manner and recovered after long-term treatment with sorafenib and sunitinib at low doses. Moreover, the expression of survivin and bcl-2 decreased after treatment with sorafenib and sunitinib was concomitant with variations in STAT3 activity. Sorafenib-induced STAT3 inhibition was mediated by regulation via MAPK pathways in HaCaT cells, while sunitinib-induced STAT3 inhibition was not. Thus, STAT3 activation mediating apoptosis suppressors may be a key factor in sorafenib and sunitinib-induced keratinocyte cytotoxicity.